The study of inertial brownian motor with fluctuating potential energy sign - Шкода, Наталия Григорьевна; Корочкова, Таисия Евгеневна; Розенбаум, Виктор Михайлович; Шапочкина, Ирина Викторовна (Eastern-European Journal of Enterprise Technologies, 2015)
The model of a Brownian motor with potential profile fluctuating in the sign, which is described by piecewise-linear periodic function, not belonging to the classes of symmetric and antisymmetric functions was presented. The model with the potential of this type shows unidirectional motion just in the case when inertialess motion is prohibited. The simplicity of the potential profile makes the problem analytically solvable and greatly simplifies the symmetry analysis. In approximations of the adiabatic mode of fluctuations and low inertia amendments, an analytical expression for the average velocity of the Brownian motor, which is different from zero only at a non-zero mass of the particle, i.e., motor effect is purely inertial was obtained. The resulting expression depends on the mass of the particle, parameters of the nonantisymmetric potential profile, the friction coefficient of the particle and temperature. It is shown that by changing the values of the parameter characterizing the profile shape deviation from antisymmetric allows to control the motion direction, and the dependence of the average velocity on this parameter is non-monotonic.